2013
DOI: 10.1093/pa/gst020
|View full text |Cite
|
Sign up to set email alerts
|

Devolution and the Limits of Tory Statecraft: The Conservative Party in Coalition and Scotland and Wales

Abstract: This article examines the territorial statecraft of the Conservative Party both internally and in the coalition government since 2010. Using Bulpitt's statecraft framework alongside some more recent work on UK intergovernmental relations, it argues that the Conservative Party has pursued broadly the same strategy as the previous Labour administration: centre autonomy management. Thus, as long as the devolved administrations and Welsh and Scottish Conservatives stick to their low politics remit, territorial pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…British territorial management was therefore a history of continuity rather than change based around a 'dual polity' whereby the national government preferred to concentrate on 'high politics'. Analyses of Scotland, Wales and Northern Ireland through a Bulpittian framework have concluded that the central autonomy model remains dominant there despite the strength of devolved powers (Bradbury, 2006;Convery, 2014). Our Bulpittian analysis continues in this historical and qualitative vein to look at the political imperatives shaping the most recent chapter in English territorial governance.…”
Section: Bulpitt's Frameworkmentioning
confidence: 89%
“…British territorial management was therefore a history of continuity rather than change based around a 'dual polity' whereby the national government preferred to concentrate on 'high politics'. Analyses of Scotland, Wales and Northern Ireland through a Bulpittian framework have concluded that the central autonomy model remains dominant there despite the strength of devolved powers (Bradbury, 2006;Convery, 2014). Our Bulpittian analysis continues in this historical and qualitative vein to look at the political imperatives shaping the most recent chapter in English territorial governance.…”
Section: Bulpitt's Frameworkmentioning
confidence: 89%
“…This emphasis on the Conservatives' historic contribution, in conjunction with the additional devolution of powers proposed by the party in the Strathclyde Commission (Scottish Conservatives, ), lends support to the arguments of Leith and Soule () concerning the Conservatives' recent conversion to support for Scottish devolution. Given the party's opposition to the introduction of the Scottish Parliament in the 1997 referendum, this stark contrast in its discourse demonstrates that there has been a move towards ‘unionist nationalism’ in the party's narratives on constitutional policy (Convery ; Ichijo ; Steven et al ). Indeed, analysis of the details of the Strathclyde Commission's proposals demonstrated a greater willingness to devolve fiscal and budgetary powers to Holyrood than Labour's Devolution Commission proposals (Thomson et al ), illustrating a swing in the party's adherence to ‘small “n” nationalism’ (Leith and Soule ) which outstrips that of Labour.…”
Section: Contemporary Political Discourse and Narratives Of Scotland'mentioning
confidence: 99%
“…This illustrates that the referendum campaign remained an opportunity for the articulation of contrasting political arguments by parties which were otherwise cooperating on constitutional matters, with the Conservatives' discourse articulating the party's Euro‐sceptic and Euro‐reformer ‘values’ in order to differentiate it from both the SNP and Labour (Anderson ; Convery ). However, these sceptical positions towards the European Union in turn highlight an ideological paradox within the Conservative's discourse, given their ideological objections to the arguments of Scottish political nationalists regarding the need for Scottish political sovereignty, whilst simultaneously making similar arguments regarding the need for enhanced British sovereignty following the loss of power to the European Union.…”
Section: Contemporary Political Discourse and Narratives Of Scotland'mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite initial success in minimising centre-periphery conflict (Convery, 2014), the Union became significantly more vulnerable by 2015. In the absence of a counter-factual, it is impossible to assess whether denying the SNP a two-question referendum and agreeing to a 2-year timescale for the referendum was a strategic error.…”
Section: Cameron and Regime Vulnerabilitymentioning
confidence: 99%